Graphene nanoplatelets in titanium coatings deposited by cold spray: Mechanical properties - Edwin Torres Díaz; Alessio Silvello; Edwin Rúa Ramirez; Rodolpho Fernando Vaz; Irene García Cano (Journal of Materials Research and Technology)
Nano-platelets Graphene (GNPs) have emerged as a promising reinforcement for Ti coatings due to their exceptional mechanical and tribological properties. This study investigates the fabrication of Titanium–Graphene Nanoplatelets (Ti-GNPs) coatings using Cold Gas Spray (CS), a technique that preserves material integrity by avoiding high-temperature degradation. Multilayer GNPs (0.5 wt%) were incorporated into Grade 1 Ti powder, followed by Heat Treatments (HT) at 700 °C and 1000 °C to enhance cohesion within the composite. Mechanical and tribological tests revealed significant enhancements in the Ti-GNPs coatings. The HT at 1000 °C increased tensile strength to 539.45 MPa and hardness to 264 HV, achieving 28% improvement compared to pure Ti. Wear tests demonstrated a 25% reduction in friction coefficient, attributed to the lubricating effect of GNPs. Microstructural analysis confirmed the successful integration of GNPs with minimal degradation, though Raman spectroscopy indicated minor structural defects at higher temperatures. These findings demonstrate that Ti-GNPs coatings provide superior mechanical performance and wear resistance, offering potential for industrial applications in extreme environments.